1991
DOI: 10.1002/anie.199108271
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Two‐Step Synthesis of N‐Acetyl‐neuraminic Acid in the Enzyme Membrane Reactor

Abstract: 1131 Crystal structure analysis of 2 : NaC,,H,,N,, Pi, u = 876.9(2), b = 988.8(4), c = 1274.1(3) pm, a = 100.52(2), fi = 94.66(2), y = 94.13(2)", V = 1078.3(5) x lo6 pm3, psalsd = 1.089 g~m -~, Z = 2, crystal size 0.3 x 0.3 x 0.9 mm3, 173 K, Cu,,, radiation, Enraf-Nonius CAD4, scan width 2.25 <8 < 76.5",4202 symmetry-independent and significant reflections [IF1 >3u(F)] structure solution by direct methods (SHELXS-86 [6]) supplemented by difference Fourier and LSQ calculations (SHELX-76) [6], 288 refined param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(68 citation statements)
references
References 18 publications
1
66
0
1
Order By: Relevance
“…Nevertheless, and in spite of the values shown in Table 2, these CLEAs are of biotechnological relevance. The apparent K M for ManNAc is lower than that reported for the enzymatic synthesis of Neu5Ac, with a K M values of 402 mM (Kragl et al, 1991), which needs concentrations about 0.7 M to reach maximum activity. On the other hand, the lower K M of pyruvate is also advantageous, since a high pyruvate concentration in the solution after the bioconversion hinders product recovery, due to the fact that pyruvate and Neu5Ac exhibit similar pKa values in the region of 2.2 (Kragl et al, 1991), making a tedious ion-change chromatography step necessary (Sugai et al, 1995).…”
Section: Kinetic Characterization Of Fastprep-cleasmentioning
confidence: 57%
See 1 more Smart Citation
“…Nevertheless, and in spite of the values shown in Table 2, these CLEAs are of biotechnological relevance. The apparent K M for ManNAc is lower than that reported for the enzymatic synthesis of Neu5Ac, with a K M values of 402 mM (Kragl et al, 1991), which needs concentrations about 0.7 M to reach maximum activity. On the other hand, the lower K M of pyruvate is also advantageous, since a high pyruvate concentration in the solution after the bioconversion hinders product recovery, due to the fact that pyruvate and Neu5Ac exhibit similar pKa values in the region of 2.2 (Kragl et al, 1991), making a tedious ion-change chromatography step necessary (Sugai et al, 1995).…”
Section: Kinetic Characterization Of Fastprep-cleasmentioning
confidence: 57%
“…In this enzymatic reaction, an excess of pyruvate over ManNAc is generally used to achieve high yield of Neu5Ac, because the equilibrium tends towards pyruvate and ManNAc (K eq , 28.7 M À1 at 25°C) (Kragl et al, 1991). For this reason, the FP-CLEAs reaction was carried out at 30°C with an almost threefold molar excess of pyruvate over ManNAc (1.4 M/0.5 M) to archive a high reaction rate.…”
Section: Potential Production Of Neu5acmentioning
confidence: 99%
“…Mehrere erfolgreiche industrielle Anwendungen gibt es zum Einsatz von Membranen, um gelöste Katalysatoren in der homogenen und Enzymkatalyse [37,38] tierungen. Wesentliche Beiträge zur Entwicklung dieses Prinzips wurden insbesondere durch Untersuchungen zur Ausschleusung des in Dehydrierreaktionen gebildeten Wasserstoffs mittels selektiver Palladium-Membranen geleistet [47,48].…”
Section: Membranreaktorenunclassified
“…Therefore, a method for the generation of NeuAc from the inexpensive monosaccharide GlcNAc in a twoenzyme system might also prove useful in regeneration schemes. It has been shown that GlcNAc can be converted to ManNAc chemically [28], or enzymatically by the action of GlcNAc-2-epimerase [29]. Recently, an overexpression system for the epimerase was developed for industrial-scale synthesis [ 301.…”
Section: Cmp-neuacmentioning
confidence: 99%